Visible-light-induced nickel-catalyzed α-hydroxytrifluoroethylation of alkyl carboxylic acids: Access to trifluoromethyl alkyl acyloins - Chen, Feng; Xu, Xiu-Hua; Chen, Zeng-Hao; Chen, Yue; Qing, Feng-Ling (Beilstein Journal of Organic Chemistry, 2023)
A visible-light-induced nickel-catalyzed cross coupling of alkyl carboxylic acids with N-trifluoroethoxyphthalimide is described. Under purple light irradiation, an α-hydroxytrifluoroethyl radical generated from a photoactive electron donor–acceptor complex between Hantzsch ester and N-trifluoroethoxyphthalimide was subsequently engaged in a nickel-catalyzed coupling reaction with in situ-activated alkyl carboxylic acids. This convenient protocol does not require photocatalysts and metal reductants, providing a straightforward and efficient access to trifluoromethyl alkyl acyloins in good yields with broad substrate compatibility. The complex bioactive molecules were also compatible with this catalytic system to afford the corresponding products.
Keywords: alkyl carboxylic acids; cross coupling; EDA complex; nickel catalysis; trifluoromethyl acyloins